2022
DOI: 10.1002/cnma.202200104
|View full text |Cite
|
Sign up to set email alerts
|

Yb3+‐Doped Phenylethylammonium Lead Bromide 2D Layered Hybrid Perovskite for Near‐Infrared Emission

Abstract: Two‐dimensional (2D) layered hybrid perovskites like phenylethylammonium lead bromide [(PEA)2PbBr4] show interesting optoelectronic properties and improved moisture stability owing to the repeating quantum‐well structure and hydrophobic organic cations, respectively. Doping metal ions in such perovskites leads to exciton‐dopant interactions, imparting new optical properties. Here we report synthesis and optical properties of Yb3+‐doped (PEA)2PbBr4. Crystals show plate‐like morphology with lateral size of few m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Consequently, the energy transfer efficiency (particularly from interior excitons) is nominal, yielding significant exciton emissivity in the PL spectrum of Mn 2+ -doped samples. We note here that recent reports suggest that doping lanthanide ions in such layered 2D perovskites is also very difficult along with inefficient host-to-dopant energy transfer. , …”
Section: Resultsmentioning
confidence: 72%
“…Consequently, the energy transfer efficiency (particularly from interior excitons) is nominal, yielding significant exciton emissivity in the PL spectrum of Mn 2+ -doped samples. We note here that recent reports suggest that doping lanthanide ions in such layered 2D perovskites is also very difficult along with inefficient host-to-dopant energy transfer. , …”
Section: Resultsmentioning
confidence: 72%
“…It is worth men-tioning that the synthesized quantum dots can be stably stored for at least 8 months in a refrigerator (under dark conditions and 4 °C) and maintain a significant PLQY of 72%, as shown in Figure 6f. Nag et al [54] reported the synthesis and optical properties of Yb 3+ doped (PEA) 2 PbBr 4 with ≈3.5 nm thin nanosheets. The intrinsic exciton emission intensity at ≈414 nm decreases systematically with increasing doping concentration (Figure 6g).…”
Section: Metal Ion Dopingmentioning
confidence: 99%
“…Nag et al. [ 54 ] reported the synthesis and optical properties of Yb 3+ doped (PEA) 2 PbBr 4 with ≈3.5 nm thin nanosheets. The intrinsic exciton emission intensity at ≈414 nm decreases systematically with increasing doping concentration (Figure 6g).…”
Section: Optical Properties Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the Yb 3+ -related NIR emission, variation in the anion composition of a host perovskite matrix helps to tune the position of their band-edge (BE) emission, making these nanostructures versatile dual-band emitters. To date, development of Yb 3+ -doped perovskite NCs included novel synthetic approaches, 21–25 applications in solar harvesting, 26,27 light detection 22 and light-emitting 28–31 devices, as well as a deeper understanding of the fundamental processes governing the photoexcitation dynamics in these nanostructures. 32,33 While TPA-excited photoluminescence (PL) from perovskite NCs has been studied in detail, less attention has been given to multiphoton-excited PL from the dopant ions, mostly limited to Mn 2+ dopants.…”
Section: Introductionmentioning
confidence: 99%